Amino acid Profile of Trichosantes cucumerina from four Geopolitical Zones in Nigeria. - Ann Nnenna Osuagwu; C.U. Aguoru; L.O. Omoigui; J.O. Olasan (Journal of Experimental and Molecular Biology, 2022)
Abstract